Killing Floor - Lee Child
Ex-military policeman Jack Reacher is a drifter. He$1 (Bs just passing through Margrave, Georgia, and in less than an hour, he$1 (Bs arrested for murder. Not much of a welcome. All Reacher knows is that he didn$1 (Bt kill anybody. At least not here. Not lately. But he doesn$1 (Bt stand a chance of convincing anyone. Not in Margrave, Georgia. Not a chance in hell.s